Re.vista: slow design como incentivo ao consumo sustentável de moda - Koswoski, Kátia (My University, 2020)
In a consumerist society, there are few thoughts about the catastrophic way of buying fast fashion and the need of a new vision of this market, highlighting the damages to the environment that this reinless consume causes. In this context, it was analyzed and reflected about the appropriate solutions when proposing a new way of clothing consumption. This job aims to present the study that has been made on the theme, by comprehending the complexity of the issue. Through studies guided by design thinking of services, it was proposed a solution based on a service with the proposal of creating a conversation with the public, promoting new experiences and strengthening the importance of a more sustainable lifestyle. [resumo fornecido pelo autor]
Em uma sociedade consumista pouco se pensa na catastrófica forma de compra de moda rápida e na necessidade de uma nova visão sobre esse mercado, ressaltando os danos ao meio ambiente que este consumo desenfreado provoca. Nesse âmbito, analisou-se e refletiu-se sobre as soluções cabíveis ao propor uma nova forma de consumo de vestuário. Este trabalho tem como objetivo apresentar o estudo feito sobre o tema, compreendendo a complexidade da questão. Por meio de estudos guiados pelo design thinking de serviços foi proposta uma solução baseada em um serviço com propósito de criar uma conversa com o público, promover novas experiências e fortalecer a importância de um estilo de vida mais sustentável. [resumo fornecido pelo autor]
Keywords: Moda; Meio Ambiente; Design